"They Burn Brightly, But Only for a Short Time": The Role of Social Workers in Companion Animal Grief and Loss. (4th March 2018) - Laing, Melissa; Maylea, Christopher
ABSTRACT: The human–animal bond is a relational theory which describes the dynamic between humans and nonhuman animals that satisfies needs in each for companionship and emotional support, framing companion animals as valued family members. Social workers have historically ignored the central role companion animals play in the lives of their clients, adopting an anthropocentric view underpinned by human rights and social justice. However, the need for companion animal-inclusive practice features in recent social work literature. As companion animals are intricately woven into the lives of their guardians, it follows that their inevitable death brings a profound sense of loss and thus an opportunity for social work intervention. The aim of this research was to see if there was a role for social work practitioners to support grieving animal companion guardians. Qualitative thematic analysis was performed on 218 candid online responses to an article on the topic of losing a companion animal, from which four major themes were identified: strength of the bond, anthropocentrically disenfranchised grief, anticipatory grief in the context of euthanasia, and the need for professional support. This analysis demonstrates the strength of the human– animal bond, illustrates how the dominant anthropocentric hegemony disenfranchises this variety of grief and loss, describes the experience of anticipatory grief in the context of euthanasia, and identifies the need for professional support. Implications for social work practice are identified, with opportunities for social workers to exchange their anthropocentric approach for a biocentric view, provide support to veterinarians and other professionals, and to work toward challenging the social constructs, which disenfranchise companion animal loss.